Numeralia Bahasa Dayak Seberuang - Lisvin Edo Pernandes; Hotma Simanjuntak; Agus Syahrani (Jurnal Mahasiswa Kreatif, 2024)
pronunciation and writing. The uniqueness of the language of the spoken numeralia Seberuang looks similar to Indonesian. However in the Seberuang language, the terms quarter, one-half, one-third are only pronounced in one word (s«simpi«?). in the Seberuang language there is only the word half (s«pia?). This study was conducted to obtain an explanation of Numeralia Bahasa Dayak Seberuang and development. This research entitled Language Numeralia Dayak Seberuang. A common problem in this research is numeralia language and its application in the learning Seberuang. The general problem, subdivided into sub-sub-problems based on 1) the type of language numeralia Seberuang, 2) form language numeralia Seberuang, 3) the function of language numeralia Seberuang, 4) the meaning of the language numeralia Seberuang. The method used in this research is descriptive method, while the shape is aqualitative research. This study illustrates the Seberuang numeralia language by native speakers of the narrative of the Seberuang.